Rescaling urban development policy in the EU: the impact of integrated place-based approaches in Cohesion Policy. Issue 6 (3rd June 2021) - Mendez, Carlos; van der Zwet, Arno; Borkowska-Waszak, Sylwia
ABSTRACT: This article investigates the role of European Union (EU) Cohesion Policy in urban development policy rescaling following the introduction of a strengthened regulatory framework for integrated territorial development in 2014–20. We find variations in the rescaling of sustainable urban development policies in the Netherlands, Poland and Spain shaped by domestic politics, path dependence and institutional capacity. The theoretical implication is that the European Commission's focus on a functional rationale for urban rescaling encounters political, policy and institutional constraints, which raises questions about the EU's capacity to shape rescaling dynamics and the need for more flexible approaches to achieve EU goals.